AN EXPERIMENTAL STUDY OF EFFECTIVE FACTORS ON SOIL REMOVAL EFFICIENCY IN CLEANING PROCESS BY SOLID STREAM JET NOZZLES - Patkavak, Mert; Koc, Yusuf; Agra, Ozden; Heperkan, Hasan (YILDIZ TECHNICAL UNIV, 2016)
Cleaning is achieved by using cleaning agents and water to remove soil, rust stains, minerals or other deposits from surfaces. Following parameters affect cleaning performance: chemical factors, water temperature, cleaning time and mechanical impact on the surfaces. This paper is related with these impacts of cleaning processes. A Water Jet Test Apparatus was used to obtain soil removal efficiency, provided by a water jet as it strikes the dirty plate under various experimental conditions. Removal efficiency of treated plate was determined by image processing technique. The percentage of soil removal of soiled spinach samples were between 25.5 and 2.2, these were a function of flow rates, angle of impact surface, cross-sectional area of nozzle, water temperature, detergent concentration and exposure time. The results show that the higher flow rate provides a greater soil removal with the same nozzle. If the cross-sectional areas of nozzles increase, the removal efficiency decreases on similar flow rate values. For same experimental conditions, the cleaning performance increases with water temperature and cleaning agent concentration. The most effective parameter on soil removal was water temperature for spinach samples. As a result of these tests, effectiveness of water temperature was 32.2%, effectiveness of detergent concentration was 19%, effectiveness of volume flow rate was 10.7%, and effectiveness of crosssectional areas of nozzle 3.6%. The remaining effectiveness of impacts was double and triple interactions. The impact of angle of jet impact surface and exposure time has limited effect on the soil removal for this experimental operating range.
Keywords: Cleaning performance; soil removal; water jet; solid stream; jet nozzles; image processing; Thermodynamics